Role of Catecholamine Hormone to Increase the Virulence of Aeromonas hydrophila - Widiantari, Ni Putu; Ramona, Yan; Julyantoro, Pande Gde Sasmita (Metamorfosa: Journal of Biological Sciences, 2023)
Extreme environmental conditions have been widely reported to trigger stress in exposed living organisms, and such conditions affect their homeostatics. Sress conditions lead vertebrates to release stress hormones, such as catecholamine Norepinephrin (NE) and Dopamine (Dopamine), which involve the hypothalamus-sympathetic-chromaffin (HSC) axis and the hypothalamus-pituitary-interrenal axis (HPI axis). These two axis systems produce catecholamine hormones (including adrenaline, noradrenaline, and dopamine) and corticosteroid hormones (especially cortisol). The presence of these two groups of hormones in the circulatory system of the hosts can act as a signal for pathogenic bacteria, such as Aeromonas hydrophilla commonly found in aquaculture, to start their infection process. These two types of hormones play a role in the expression of Aeromonas hydrophila genes encoding formation of flagella (allowing bacterial cells to swim rapidly to their host), pilli, toxin production, and activation of biofilm formation process. The stress conditions experienced by fishes (which triggers the secretion of catecholamine hormones) can significantly reduce the fish's immune system to function, and this will be exploited by Aeromonas hydrophila to increase its metabolic rate, growth, and virulence in such stressed fish. Specifically, catecholamine hormones can also act as a signal for the Aeromonas hydrophila to activate the ferric uptake regulator gene ( fur gene), allowing this pathogenic bacterium to optimally chelate ions of iron (Fe 3+ ) from its environment, resulting in the excessive growth of the pathogen and an increase in its pathogenicity.